2011
DOI: 10.1016/j.jbi.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Improving MeSH classification of biomedical articles using citation contexts

Abstract: Medical Subject Headings (MeSH) are used to index the majority of databases generated by the National Library of Medicine. Essentially, MeSH terms are designed to make information, such as scientific articles, more retrievable and assessable to users of systems such as PubMed. This paper proposes a novel method for automating the assignment of biomedical publications with MeSH terms that takes advantage of citation references to these publications. Our findings show that analysing the citation references that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…For example, NLM has implemented automated methods to assist human indexers, and other efforts have been exerted to improve both the expediency and the accuracy of the indexing process. 3,11,12 Preliminary findings from this analysis indicated that journal identity was significantly associated with time to indexing and that the methodological quality of articles did not appear to influence the time to indexing. Perhaps a protocol directing that indexing be based on publication characteristics that indicate methodological quality, provided to NLM by authors, would help facilitate more rapid identification of practice-changing publications.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, NLM has implemented automated methods to assist human indexers, and other efforts have been exerted to improve both the expediency and the accuracy of the indexing process. 3,11,12 Preliminary findings from this analysis indicated that journal identity was significantly associated with time to indexing and that the methodological quality of articles did not appear to influence the time to indexing. Perhaps a protocol directing that indexing be based on publication characteristics that indicate methodological quality, provided to NLM by authors, would help facilitate more rapid identification of practice-changing publications.…”
Section: Discussionmentioning
confidence: 81%
“…1,2 There are over 26,000 MeSH terms for unique concepts, including disease states, drugs, and publication characteristics such as type of article or research (e.g., randomized controlled trial [RCT], case report) and type of research funding, which are curated by the NLM's Medical Subject Headings Section staff. 3 Searches of the medical literature that use only plaintext search terms (i.e., search terms that do not invoke an algorithmic search function) may omit relevant results from articles that use terminology different from words inputted by the searcher. With MeSH terms, clinicians can search for concepts rather than plaintext search terms, obtaining more relevant results on the same topic, albeit with different terminology.…”
mentioning
confidence: 99%
“…The authors use the text surrounding the references to extend the text representation for document clustering. The proposed approach has been also used for text classification in the medical domain (Ortuño et al, 2013), where it showed an improvement of processing results in comparison to the typical content-based representations (Aljaber et al, 2011).…”
Section: Combined Representationmentioning
confidence: 99%
“…They collected the top-ranked documents in retrieved sets to generate aspect queries. Aljaber et al used terms of citation contexts and UMLS to improve the MeSH classification [39]. Considering the same information, Ortuno et al exploited cited references to support the retrieval of related biomedical documents [40].…”
Section: Related Workmentioning
confidence: 99%